Sansevieria trifasciata Properties as Lead(II) Ion Biosorbent - Yuningsih, Lela Mukmilah; Batubara, Irmanida; Darusman, Latifah Kosim (Makara Journal of Science, 2014)
Sansevieria trifasciata (also called snake plant or mother in law’s tongue) is predicted to act as a heavy metal biosorbent. S. trifasciata was optimized as a biosorbent by using the response surface method with varying weights of S. trifasciata, pH of Pb (II) solutions, contact times, and temperatures. The ion concentration before and after biosorption was measured with an atomic absorption spectrophotometer (AAS). The optimum biosorption conditions were pH 7, 240 min contact time, and 1.5 g biosorbent with biosorption capacity of Pb (II) ions 0.725 mg/g. The biosorption isotherm analysis showed that the biosorption is consistent with the Freundlich isotherm model. The peak intensity of the FTIR spectrum of S. trifasciata after treatment with Pb (II) was around 2130/cm. The S. trifasciata micrograph showed a porous structure with non-uniform pore sizes. The biosorption of Pb (II) ions on powdered S. trifasciata leaves was found with the SEM EDX analysis. It is concluded from this research that S. trifasciata can be used as a biosorbent to remove Pb ion contamination.